The design of unsurfaced roads using geosynthetics - Little, Peter H. (1993)
Current available methods for the design of unpaved roads, with and without geosynthetics, were used for sixteen full-scale test sections which were constructed at the Bothkennar Soft Clay Site, Airth, Scotland. The full-scale trials consisted of twelve pavements including geosynthetics and four control pavements incorporating two types of aggregate and two design life expectancies. The test pavements were instrumented to monitor the transient stress and strain distribution, permanent strain distribution, geosynthetic temperature and ground water level during the trafficking operation. Traffic loading was provided in two stages by a standard road-going vehicle. The vehicle used for Phase One applied an 80kN axle load and in Phase Two a 126kN axle load. Failure of the pavements was defined as a rut depth of 150mm. The passage of 2115 axles resulted in failure of three sections and significant deformations in many others. Back-calculation to compare predicted and measured performance was performed and hence the existing design methods were critically assessed. Where possible the measurements obtained from field trials were used to examine the assumptions made within the design methods. The existing design methods were found to be essentially static in approach and did not model transient stresses and strains or permanent strain development adequately. Pointers towards a new approach ensuring strain compatibility between the elements of the system are suggested. This should enhance the ability of the engineer to assess the value of differing products used in this application.